PERSEPSI PEMUDA ISLAM TERHADAP KEBIJAKAN ERDOGAN PADA KONFLIK PALESTINA-ISRAEL - Donny Pramudya Mahardi (UNIVERSITAS PAKUAN, 2021)
Erdogan has a political movement based on Islamic politics. Erdogan issued a range of political policies inherent in Islamic identity. This shaped Erdogan's image as a world-Islamic figure who represented the interests of the Islamic world. Erdogan's policy on the Palestinian-Israeli conflict in 2021 strengthens Erdogan as an Islamic leader. The study examined Erdogan's foreign policy in favor of Palestine in the context of the Israeli-Palestinian conflict and analyzed perceptions of Muslim youth as implications for that policy. The study analyzed foreign policy strategies that stakeholders can use in shaping public perception of him. The study uses a mix of desk study and empirical approaches. Data collection is carried out by (1) reviewing the literature of previous research results and (2) distributing questionnaires to the board of Islamic student organizations at IPB University as respondents. Based on the results of the analysis, the influence of Erdogan's policies on his support of Palestine has a strong impact on young Muslims in Indonesia. Respondents perceived that Erdogan is an Islamic leader who meets the expectations of the world's Muslims.